Modeling commuting patterns in a multi-regional input–output framework: impacts of an ‘urban re-centralization’ scenario - Ferreira, Joao-Pedro (2017)
The paper suggests a modeling approach for assessing economic and social impacts of changes in urban forms and commuting patterns that extends a multi-regional input–output framework by incorporating a set of commuting-related consequences. The Lisbon Metropolitan Area case with an urban re-centralization scenario is used as an example to illustrate the relevance of this modeling approach for analyzing commuting-related changes in regional income distribution on the one side and in household consumption structures on the other.